Upaya Meningkatkan Pemahaman Konsep Siswa Pada Materi Sistem Tata Surya Dengan Menggunakan Media Ular Tangga - Fifit Andriyani; Rizki Hadiwijaya Zulkarnaen; Febri Fajar Pratama (Jurnal Bintang Pendidikan Indonesia, 2023)
This research was motivated by the low understanding of the concept of science in class VI students at SDN Pusparaja, pre-action data stated that out of a total of 21 students only 6 (28.57%) students understood the lesson well and 15 (71.42%) students had an understanding very good. understanding of the concept is low Meanwhile, for science learning in class VI of SDN Pusparaja science learning must be able to achieve a score of 68. This study aims to identify and analyze planning, implementation, and increasing understanding of science concepts using snakes and ladders media. . This type of research is classroom action research (CAR), with planning, action, observation, and reflection research procedures. Data collection techniques using observation, interviews, and tests. Based on the results of the study showed that learning using snakes and ladders media can improve students' understanding of concepts in science learning about the solar system. The results of the study concluded that students' conceptual understanding in science learning with snakes and ladders media in class VI of SDN I Pusparaja was able to increase. This increase before using the snakes and ladders media (pre-action) obtained an average score of 56.66 with a completeness percentage of 28.57% in the "less" category. .90% category "good" Then in cycle II obtained an average value of 73.33 with a percentage of 80.95% category "good". So that the use of snakes and ladders media is very well applied in classroom learning and is able to increase students' understanding of concepts in science learning about the solar system.